Enzymatic response of mungbean (Vigna radiata) genotypes against Cercospora leaf spot disease - BHARTI, MAMTA; CHANDRA, RAMESH; KUMAR, AJAY; KUMAR, RAHUL; YADAV, VIKAS; YADAV, PRAKASH (The Indian Journal of Agricultural Sciences, 2017)
Mungbean (Vigna radiata L.) is one of the most valuable pulse crops grown in India. Mungbean suffers from several diseases with substantial losses in yields. Among the diseases, mungbean leaf spot disease is the most destructive which is caused by Cercospora canacens and cause heavy loss (0-61%) in yield in Indian subcontinent and adjacent areas of South-East Asia. An experiment was conducted to find out the enzymatic response of various genotypes of mungbean against Cercospora leaf spot. The level of antioxidant enzyme SOD, peroxidase and catalase increase in both susceptible and resistance cultivar, but in resistance cultivar the level these enzymes increases very rapidly as compare to susceptible cultivar. Based on the various observations, it can be interprets that in resistant cultivar, the higher level of ROS produced after inoculation is minimized up to optimum level by the action of these enzymes SOD, peroxidase and catalase, but not in susceptible cultivar. Plants show resistance or susceptibility for disease is due to the activity of SOD, peroxidase, and catalase. In F2 generation plants show segregation pattern in the ratio of 1:2:1 which depicts that the gene governing the enzyme activities are partial dominant in nature.